Learning Reflection Using Realistic Mathematics Education Assisted by GeoGebra Software - Hardiyanto, Dwi; Asokawati, Indhi; Majid, Panji Maulana; Maesaroh, Atika Tri; Nursyahidah, Farida (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Reflection material is very important for students to master when studying transformation material. However, reflection material is still difficult for students to understand. Therefore, this research aims to create a learning trajectory that can help students understand the concept of reflection using the context of the Tedhak Siten tradition with the help of GeoGebra software in grade 9th of SMP Negeri 6 Semarang. This research uses a design research method consisting of three stages: preliminary design, design experiment, and retrospective analysis. In this research, a series of learning activities were designed and developed based on the (Realistic Mathematics Education) RME approach. This research involved 6 grade 9th students. The result of this research is a learning trajectory that includes a series of learning processes in three activities, namely: 1) Observing the Tedhak Siten tradition video to find the definition and characteristics of reflection; 2) Finding formulas and reflection results; and 3) Resolving contextual problems related to reflection. The conducted activity can aid in improving students’ comprehension of reflection material. The research results showed that students could discover the characteristics and definitions of reflection, find formulas and reflection results, and solve contextual problems related to reflection.